2005
DOI: 10.1007/s00018-005-5017-3
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effect of β-elemene in non-small-cell lung cancer cells is mediated via induction of cell cycle arrest and apoptotic cell death

Abstract: Beta-elemene is a novel anticancer drug, which was extracted from the ginger plant. However, the mechanism of action of beta-elemene in non-small-cell lung cancer (NSCLC) remains unknown. Here we show that beta-elemene had differential inhibitory effects on cell growth between NSCLC cell lines and lung fibroblast and bronchial epithelial cell lines. In addition, beta-elemene was found to arrest NSCLC cells at G2-M phase, the arrest being accompanied by decreases in the levels of cyclin B1 and phospho-Cdc2 (Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
161
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(171 citation statements)
references
References 48 publications
(58 reference statements)
5
161
0
5
Order By: Relevance
“…Studies indicate that ß-elemene is a broad-spectrum anticancer agent, with efficacy in treating leukemia, brain tumor, breast cancer and liver cancer (13)(14)(15)(16)(17). Recently, ß-elemene has been shown to induce tumor cell apoptosis and cell cycle G2/M arrest, as evidenced by DNA ladder formation, morphological alterations and flow cytometric data; these findings suggest that apoptosis and G2/M arrest triggered by ß-elemene contribute to its inhibition of cell proliferation (13)(14)(15)(16)(17)(18). ß-Elemene has also been shown to decrease the level of Bcl-2, an anti-apoptotic protein (18).…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that ß-elemene is a broad-spectrum anticancer agent, with efficacy in treating leukemia, brain tumor, breast cancer and liver cancer (13)(14)(15)(16)(17). Recently, ß-elemene has been shown to induce tumor cell apoptosis and cell cycle G2/M arrest, as evidenced by DNA ladder formation, morphological alterations and flow cytometric data; these findings suggest that apoptosis and G2/M arrest triggered by ß-elemene contribute to its inhibition of cell proliferation (13)(14)(15)(16)(17)(18). ß-Elemene has also been shown to decrease the level of Bcl-2, an anti-apoptotic protein (18).…”
Section: Introductionmentioning
confidence: 99%
“…leaves was determined (Moura et al, 2006). Despite not being preponderant, the oil analyses showed that among its numerous constituents, there are some components described in literature as cytotoxic substances against tumoral cells, such as β-caryophyllene (5.9%), β-elemene (3.1%), δ -elemene (1.6%), α-humulene (2.3%) (Duh et al, 1999;Legault et al, 2003;Sibanda et al, 2004;Sylvestre et al, 2005;Stravi et al, 2005;Tatman and Mo, 2002;Wang et al, 2005;Sylvestre et al, 2006;Hou et al, 2006;Tao et al, 2006;Xiao et al, 2006. Some other components with no or low antitumoral activity were also found in this species, eg sphathulenol (3.8%), á-pinene (6.4%), linalool (0.5%), myrcene (0.6%) (Fullas et al, 1994;Tatman & Mo, 2002;Stavri et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that elemene is a promising agent for the treatment of tumours. b-Elemene, the major active component of elemene, has been shown to be effective against various tumours such as lung cancer, prostate cancer and glioblastoma (Wang et al 2005;Yao et al 2008;Li et al 2010).…”
Section: Gc-ms Analysis Of Essential Oilmentioning
confidence: 99%